Original papersPolymorphism of the vascular endothelial growth factor gene and susceptibility to basal cell carcinoma – preliminary study - Sobjanek, Michał; Zabłotna, Monika; Michajłowski, Igor; Urban, Marek; Nedoszytko, Bogusław; Mędrzycka-Dąbrowska, Wioletta; Włodarkiewicz, Adam; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: The vascular endothelial growth factor (VEGF) is involved in pathologic angiogenesis in several neoplasms. Several functional single nucleotide polymorphisms (SNPs) in the promoter region have been described. It has been suggested that -1154G/A polymorphism is associated with VEGF expression. Aim: The aim of our study was to evaluate the connection between -1154G/A VEGF gene polymorphism and BCC susceptibility. Material and methods: We analyzed 100 patients with BCC and 240 healthy controls. The -1154G/A polymorphism in the promoter region of the VEGF gene was analyzed by amplification refractory mutation system-polymerase chain reaction. The result was evaluated by the c2 test with Yates correction. Results: We have found that AA genotype frequency was significantly decreased among patients with BCC in comparison with control subjects (3 vs. 16.2%, p = 0.0014). We also found that VEGF-1154 A allele frequency was significantly decreased among patients with BCC in comparison with control subjects (30.5 vs. 40.0%, p = 0.0246). Conclusions: This is the first report concerning VEGF gene polymorphism and BCC. Presented data suggest that the SNP at position -1154 of the promoter region of the VEGF gene may play a role in pathogenesis of BCC.